Ketidakamanan Manusia Pasca Pandemi Covid-19: Studi Kasus Indonesia - Mas’udi, Syasya Yuania Fadila; Alamsyah, Fajar (Global and Policy Journal of International Relations, 2022)
ABSTRACTIndonesia as a developing country has many problems that cause human insecurity, such as for example the lack of adequate health facilities, especially in areas outside Java, environmental problems such as plastic pollution in the oceans which indirectly also has a negative impact on health, as well as some difficulties in economic growth. The state of insecurity felt by the Indonesian people got worse when the Covid-19 pandemic hit Indonesia, this is evidenced by the many fatalities and increasing unemployment due to the pandemic. After about two years of being hit by a pandemic, Indonesia is currently entering a post-pandemic year where all sectors have recovered, especially in these three sectors. This research wants to see whether the Indonesian people are still facing insecurity in the health, environment and economic sectors after the Covid-19 pandemic. The results of the study found that even though Indonesia has started to rise, the legacy of insecurity, especially in these three sectors, is still being felt by the majority of Indonesian people. This is evidenced that in the health sector, improvements in health facilities are still not optimal, in the environmental sector, the Indonesian people are actually facing a new pollution problem, namely mask pollution, and in the economic sector, the number of unemployed people who increased during the pandemic has not been fully employed.Keywords: human insecurity, economy insecurity, health insecurity, environmental insecurity, Indonesia, post-pandemic Covid-19DOI: https://doi.org/10.33005/jgp.v10i02.3751